2011
DOI: 10.1158/0008-5472.can-10-4246
|View full text |Cite
|
Sign up to set email alerts
|

CD73-Deficient Mice Have Increased Antitumor Immunity and Are Resistant to Experimental Metastasis

Abstract: CD73 is a cell-surface enzyme that suppresses immune responses by producing extracellular adenosine. In this study, we employed CD73 gene-targeted mice to investigate the role of host-derived CD73 on antitumor immunity and tumor cell metastasis. We found that CD73 ablation significantly suppressed the growth of ovalbumin-expressing MC38 colon cancer, EG7 lymphoma, AT-3 mammary tumors, and B16F10 melanoma. The protective effect of CD73 deficiency on primary tumors was dependent on CD8 þ T cells and associated w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
346
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(380 citation statements)
references
References 37 publications
(39 reference statements)
23
346
1
3
Order By: Relevance
“…This result is in agreement with the literature that shows the increase of ecto-5′-NT/CD73 expression in many other cancers such as breast cancer, glioma, and melanoma [19,23,56]. Furthermore, ecto-5′-NT/CD73 overexpression promotes invasion, migration, adhesion, and metastasis of human breast cancer cells [20,57], indicating higher invasiveness and metastatic capability to melanomas [56,58] and poor prognosis in human colorectal cancer [22]. Ecto-5′-NT/CD73 expression in cancer cells has been also linked with drug resistance [26,59] and immune escape [44,60].…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with the literature that shows the increase of ecto-5′-NT/CD73 expression in many other cancers such as breast cancer, glioma, and melanoma [19,23,56]. Furthermore, ecto-5′-NT/CD73 overexpression promotes invasion, migration, adhesion, and metastasis of human breast cancer cells [20,57], indicating higher invasiveness and metastatic capability to melanomas [56,58] and poor prognosis in human colorectal cancer [22]. Ecto-5′-NT/CD73 expression in cancer cells has been also linked with drug resistance [26,59] and immune escape [44,60].…”
Section: Discussionsupporting
confidence: 92%
“…Stagg et al and Zhou et al found that CD73, the ectoenzyme responsible for endogenous adenosine formation, contributes to breast cancer metastasis [15][16][17]. In agreement with these reports, we found that MDA-MB-231 cells overexpress CD73 and differ from HMEC in that they possess more efficient means than HMEC to hydrolyze extracellular ATP to adenosine (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the ATP breakdown product adenosine can activate calcium signaling in MDA-MB-231 breast cancer cells, and the ectonucleotidase C D 7 3 , w h i c h c o n v e r t s e x t r a c e l l u l a r a d e n o s i n e monophosphate (AMP) to adenosine, was shown to promote breast cancer growth and metastasis [15][16][17]. In light of our previous work, these reports support the concept that purinergic signaling can indeed contribute to the motility and metastasis of breast cancer cells.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Other groups also reported the association between CD73 expression and metastasis in breast cancer cell lines and CD73-/-mice (20). In this study, we further explored the clinical significance and potential mechanisms of CD73 in breast cancer by IHC on TMAs.…”
Section: Discussionmentioning
confidence: 84%
“…Adenosine, acting through G-protein coupled receptors, plays an important role not only in immune suppression but also in malignant behavior of tumor cells (18). CD73-deficient mice are resistant to the development of 3-methylcholanthrene (MCA)-induced fibrosarcomas through a mechanism relying on IFN-c, natural killer (NK) cells, and CD81 T cells (19), while treatment with a selective inhibitor a,b-methylene ADP (APCP) or anti-CD73 monoclonal antibody significantly reduced tumor growth and metastasis (20). Although many of the CD73 effects are consequences of its adenosine production, also more direct interactions have been reported.…”
Section: Discussionmentioning
confidence: 99%